The Light and Shadow Brought to Teacher Education by Digitizing the Educational Environment: The Case of Japan - Toshiyuki Kihara (MDPI AG, 2021)
In this paper, the trends and issues of teacher education research and practices in Japan are clarified from the viewpoint of the digitization of the educational environment. This will be achieved through a review of the literature and policy documents on recent educational practices and teacher education. Firstly, Japanese teacher education and the ICT environment in schools are summarized. In addition, the Japanese concept of "teachers who continue to learn" and its multidimensional character is explained. Secondly, a model of the above idea that consists of five dimensions is introduced: (1) social navigators, (2) technical experts, (3) inquiry practitioners, (4) critical practitioners, and (5) members of professional learning communities. Thirdly, through the review, it is pointed out that all of them are affected by the digitization of the educational environment, which has been accelerated as a countermeasure to COVID-19. In conclusion, it is stated that the digitization of the educational environment and its accelerated progress casts both light and shadow on the role of Japanese teachers as reflective practitioners. Additionally, it is referenced that there are many differences among schools and regions on the ratio of light and shadow in Japan, even though it is geographically small.